Dietary intake and risk assessment of nitrosamine in processed meat products among medical staff during their night shift - Dalia Ibrahim Tayel; Noorhan K. Farrag; Samar Mohamed Aborhyem (Scientific Reports)
Abstract The study aims to evaluate the levels of nitrosamine, a known carcinogenic compound, in processed meat products and to assess its dietary intake and margin of exposure among medical staff, including physicians, pharmacists, and nurses working night shifts at Alexandria University Hospitals. Additionally, the study seeks to evaluate the participants’ knowledge of dietary sources and regulatory limits of carcinogens. A cross-sectional study was conducted with 420 participants. Results showed that hotdogs contained the highest nitrosamine levels (159.24 ± 87.99 µg/g) with a consumption pattern of 0.02126 µg/kg BW/day. In contrast, sausages and burgers had the lowest nitrosamine content (2.36 µg/g and 2.37 µg/g, respectively). Luncheon meat also exhibited low nitrosamine levels and consumption patterns, at 18.53 µg/g and 0.00141 µg/kg BW/day, respectively. The Margin of Exposure (MOE) was calculated to assess risk, with a Benchmark Dose Lower Confidence Limit (BMDL)10 value of 29 µg/kg BW/day as the reference point. MOE values ≥ 17,000, derived for nitrosamine exposure in this study, indicate a low level of concern for carcinogenic risk. A statistically significant difference in dietary nitrosamine intake was observed across different professions among the medical staff (p < 0.001).